SYMBOLIC THINKING SKILLS: MEANING WRAPS, SOCIETY AND ICTS - Romero Morett, Miguel A.; Forero Romero, Aracely; Cedano Rodríguez, Alfredo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
The objective and content of this intervention has its core in mentioning the problems of the construction of a symbolic thinking in the context of a society defined by ICTs, which at the same time configure the current identity of the human kind, creator and by its own right of the meaning and creation of sense of the human events and natural phenomena. Particularly regarding the Access to this problem mentioning, it has its source in the implementation of the conjunction among authors, the recovery of the teaching experience in the Monterey Master’s degree on Humanistic Studies and in the Department of Philosophy at the Universidad de Guadalajara, and the quantitative checking on the importance of the usage of ICTs in Mexico and the state of Alisco, with this a triangle whose corners come in contact with one and other.